A novel synergistic and eco-friendly approach for efficient crude oil removal from water using ZnO/g-C3N4/chitosan nanostructure and spirulina algae - Solat Gandomi Niyat; Fariba Zamani Hargalani; Mozhgan Emtyazjoo; Fatemeh Yazdian; Ali Mashinchian Moradi (Scientific Reports)
Abstract This study highlights the effectiveness of a ZnO/g-C3N4/chitosan nanocomposite as an eco-friendly adsorbent for removing naphthalene from water. Synthesized via calcination, co-precipitation, and hydrothermal methods, the composite integrates ZnO nanoparticles, g-C3N4 nanosheets, and chitosan to create a material with synergistic adsorption properties. Structural analyses (FTIR, XRD, FESEM, TEM, BET) confirmed its mesoporous nature, with a surface area of 1.33 m2/g and average pore size of 11.92 nm. Despite a slight reduction in surface area caused by chitosan incorporation, the nanocomposite achieved a maximum removal efficiency of 90% and an adsorption capacity of 9.87 mg/g under optimal conditions (pH 6.8, adsorbent dosage of 81 mg/L, initial naphthalene concentration of 5 mg/L, and contact time of 180 min. The Langmuir model (R2 > 0.97) indicated monolayer adsorption, while thermodynamic parameters confirmed an exothermic and spontaneous process. Kinetic modeling favored the pseudo-first-order model, suggesting physical adsorption dominates. Although the performance declined in seawater (39%), it improved to 50% with the addition of Spirulina algae, and achieved over 99% in synthetic solutions. Regeneration tests showed chemical methods were more effective than thermal approaches across six cycles. Overall, the nanocomposite demonstrates suitable potential for naphthalene and PAH remediation, though further enhancement is needed for real-world water treatment applications.